Progressive trends in prenatal genetic screening - Kirolos S. Eskandar (Universitas Syiah Kuala, 2023)
According to the global report on birth defects in 2021, it is estimated that 8 million children are born with birth defects of genetic origin annually. These birth defects vary in their degree of severity; where some types are mild and don’t require treatment but others may necessitate lifelong medications or even cause instant death just after birth. That is why prenatal screening is doubtless necessary to detect such genetic defects before birth aiming to drop the tragedy of these children off. Recently, this approach has been developing towards non-invasive techniques that reduce the risk of miscarriage which was common in the old-fashioned invasive ones. Non-invasive Prenatal Tests (NIPTs) like Chromosomal Microarray Analysis (CMA) and cell-free fetal DNA (cffDNA) caused a breakthrough in the screening methods of chromosomal aneuploidies. Thanks to their benefits, NIPTs are considered a fundamental clinical approach for pregnant women’ screening in multiple countries. Thence, this paper gives prominence to the recentness of NIPTs along with each’s assets, liabilities, and prospective recommendations. In addition, it would demonstrate the importance of modern molecular technologies like next-generation sequencing (NGS) which are enforced for the appliance of NIPTs.